Participatory Budgeting's Impact on Managerial Performance: The Mediating Role of Goal Commitment: Dampak Partisipatif Anggaran Terhadap Kinerja Manajerial: Peran Mediasi Komitmen Tujuan - Nabilla, Dewi Ayu; Fitriyah, Hadiah (Universitas Muhammadiyah Sidoarjo, 2023)
This study investigates the relationship between participatory budgeting and managerial performance, with a focus on the mediating role of goal commitment. Utilizing purposive sampling, data was collected from 65 respondents via Google Forms and analyzed using the Outer Model to assess data validity and reliability. Subsequently, the Inner Model was employed to test hypotheses through SmartPLS 3.0. Results indicate a significant influence of participatory budgeting on both managerial performance and goal commitment. However, goal commitment was found to have no direct impact on managerial performance, and it did not mediate the relationship between participatory budgeting and managerial performance. This research underscores the importance of participatory budgeting in enhancing managerial performance while highlighting the need for further exploration of the mechanisms underlying this relationship. Highlights: Participatory budgeting's significant influence: This study uncovers the substantial impact of participatory budgeting on managerial performance. Role of goal commitment: It examines the role of goal commitment as a mediating factor in the participatory budgeting and managerial performance relationship. Implications for organizational effectiveness: The research highlights implications for organizations aiming to enhance their effectiveness through participatory budgeting strategies. Keywords: Participatory budgeting, Managerial performance, Goal commitment, Mediation, Organizational effectiveness